Changing definitions of euphoria in multiple sclerosis: A short report. (May 2015) - Duncan, Amy; Malcolm-Smith, Susan; Ameen, Ozayr; Solms, Mark
A recent interest in euphoria in multiple sclerosis (MS) has resulted in a wealth of literature on this topic. However, a marked change in the definition of this symptom appears to have taken place since its first descriptions in the mid-19 th century. This short report will demonstrate that the 'euphoria' being studied today may not be the same state as that originally observed and described in MS patients and some implications of this possibility are discussed.